THE INFLUENCE OF LIFESTYLE, FINANCIAL TECHNOLOGY, FINANCIAL LITERACY, AND FINANCIAL BEHAVIOR ON GENERETION Z INVESTMENT DECISIONS - SAPTYANA, RISKA FITA (DIPONEGORO UNIVERSITY, 2023)
This research aims to examine the influence of lifestyle, financial technology, financial literacy, and financial behavior on investment decisions among generation Z students in Semarang. The respondents in this research were 202 Generation Z students in Semarang. The primary data used in this research was by distributing research online questionnaires and processed using SPSS statistics 26. The results of this research show that lifestyle, financial technology and financial behavior have a positive and significant influence on generation Z's investment decisions. Meanwhile, financial literacy has no effect. significant impact on generation Z's investment decisions